Fixed point results in tricomplex valued fuzzy metric spaces with application - Tiwari , Rakesh; Rajput, Shraddha (International Journal of Engineering and Technology, 2024)
In this article, accredit the innovative concept of complex valued the fuzzy set due to Ramot et al.[17], Singh et al.[20] and Choi et al.[7], we introduce the conceptualisation of tricomplex valued fuzzy metric spaces and this paper is inspired by Ismat Beg et al.[10]. Various related topological features have been established for tricomplex-valued fuzzy metric spaces, thereby reinforcing the foundational concept.